SISTEM INFORMASI PENJUALAN DAN PEMBELIAN UNTUK MENYUSUN DAN MENGUKUR RASIO PROFITABILITAS - Muhamad Sidik; Nailin Niklis (CV. ALIM'SPUBLISHING, 2023)
The development of technology today has become something that is universal and can be used in various human lives. One of them is in business. In today's era, it is undeniable that a computer is a component that must be owned by a company in running its business, in order to assist in processing data and help improve the quality of work and quality in service. In this case, Toko Maju Jaya is used as a place of research, because in this place the system that is carried out is still manual and has not been managed properly, so errors often occur in making reports and in processing stock items. The purpose of this study is to provide convenience during the processing of sales, purchase transactions, goods data, supplier data and customer data, minimizing errors in recording. The research method used in this research is using the R&D (Research and Development) method. This method is used to produce a certain product that is analytical and can be tested for effectiveness so that it can be used in the wider community. In designing the system the tools used are Flowcharts, Entity Relationship Diagrams and Context Diagrams, while for data collection using observations, interviews, and literature studies. The database application development tool uses MySQL and the programming language uses Visual Basic 6.0. With this information system transaction data processing can be done computerized so as to reduce errors in reporting.